The Combined Effect of Bubble and Photo Catalysis Technology in BTEX Removal from Produced Water - Marwah Al-Nuaim; Asawer A. Al-Wasiti; Zainb Y. Shnain; Abbas K. Al-Shalal (Bulletin of Chemical Reaction Engineering & Catalysis, 2022)
Among the several ways used in wastewater treatment, the photocatalysis process is a more novel and alternative process that is increasingly employed in recent years. This work aims to improve the performance of the photocatalyst process by using air bubbles in removing the BTEX from produced water as an indicator of process efficiency. The study also shows the effect of influencing factors (pH and residence time) on the photocatalysis process. The study was done in a rectangular column with dimensions of 200 mm width, 30 mm depth, and 1500 mm height. Commercial titanium oxide (TiO2) coated on a plate by the varnish was used as a source of the photocatalyst. The experiment was carried out under different values of gas flow rate (0-3 L/min) to evaluate its effect on the photocatalyst process, the effect of other variables of pH (3-11), and irradiation time (30-120) min was also studied. A new method of the coating was adopted by using an alumina plate with varnish as an adhesive. The characteristics results show that the coated plate has hydrophilic properties and that there is no significant change in the crystal structure of the TiO2 nanoparticles and the varnish before and after 60 h of the photocatalytic process, indicating that the plate is still effective after 60 h usage under different conditions. The results also show that the introduction of air bubbles enhances the removal efficiency of BTEX significantly and the best removal effectiveness of BTEX was 93% when pH = 5 after 90 min and 90% when pH = 3 after 120 min. The removal rate also reached 86% when pH = 7 after 120 min all at a flow rate of 3 L/min. The percentage of removal decreased at pH = 9 and 11, reaching 64% and 50%, respectively after 120 min and a flow rate of 3 L/min. Copyright © 2022 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).